Video Game Characters and Transmedia Storytelling The Dynamic Game Character - Blom, Joleen (Games and Play, 2023)
Characters are a vital aspect of today's transmedia practices. Combining theories on fictional persons from Japanese and Euro-American practices, this book discusses video game characters embedded in our popular media culture in which they are constantly produced and re-imagined. This book introduces the dynamic game character, a type of game character with a development structure that consists of multiple outcomes in a game. Through their actions and choices, players can influence these game characters' identities and affect their possible destinies. Games subvert the idea that fictional persons must maintain a coherent identity. This book shows that dynamic game characters challenge strategies of top-down control through close readings of the Mass Effect series, Persona 5, Hades, Animal Crossing: New Horizons and more. It is directed to all scholars interested in the topics of transmedia storytelling, video games, characters, and Japanese narratology.